Analisis Proses Administrasi Perjalanan Dinas Di Sekretariat Dewan Perwakilan Rakyat Daerah Provinsi Sumatera Selatan - Immaculata Yovita Adventy, Maria; Azhar, Azhar; Putra, Raniasa; Azhara Putri, Cynthia (PERSPEKTIF, 2024)
This research aims to find out how the administrative process of official travel at the Secretariat of the Regional House of Representatives of South Sumatra Province. The problem is focused on the administrative process of implementing official travel. To approach this problem, a reference to Max Ammerman's 1998 Root Causal Analysis theory is used. Data were collected through observation and in-depth interviews and analyzed qualitatively. This study concludes that official travel can be carried out by council members as well as civil servants and non-civil servants, and the administrative process of official travel consists of three administrative processes, namely the administrative process of implementing official travel by civil servants and implementation by council members, the administrative process of accountability and the administrative process of payment or disbursement of reimbursement by the treasurer of routine expenses to the executors of official travel. This study concludes that there is one official travel administration process that is considered less effective, namely the accountability administration process, this happens because there are several official travel executors who take a long time to deposit the cost details to the finance department, or this delay is considered not to have implemented South Sumatra Governor Regulation Number 5 of 2021 concerning Guidelines for the Implementation of Official Travel within the South Sumatra Provincial Government chapter ix article 34.